Pakistan’s Dual Crisis: Floodwaters and public health emergency - Amir Sultan; Usama Siddique; Dr Muhmmad Asif (Journal of the Pakistan Medical Association, 2025)
Pakistan is consistently ranked among the top 5 countriesprone to climate change mentioned by the United NationsHabitat in 2023, while the country is ranked 7th mostvulnerable to climate change and 8th most affectedcountry by climate change according to the German GlobalClimate Risk Index (GCRI).1 Pakistan is a land that hasdeserts, glaciers, mountains, and coastal regions, but dueto insufficient infrastructure, lack of preparedness andplanning, and poor functional skills, it is more vulnerableto natural disasters like floods.2 The intensity and numberof flood events and flash floods have notably increased inPakistan, a phenomenon of concern. There were 21 floodevents from 1950 to 2010 but the super flood of 2010caused 1985 deaths and displaced 20 million people. Thesecond catastrophic flood of the monsoon hit Pakistan in2022 and caused the deaths of 1033 people, affected 33million people, and displaced 5.4 million people.3 NowKhyber Pukhtankhwa was hit by the historic worst flashflood, while the eastern province of Punjab faced thebiggest flood in its history. Due to that, the level of thethree rivers rose and submerged 2300 villages, andaccording to the National Disaster Management Authority(NDMA), 881 people were killed, 1100 injured, and 1.5million displaced as a result of torrential monsoon rains andfloods.4 Continue...